Analisis Nilai Tambah dan BEP Kacang Garing Sihobuk di Desa Silangkitang Kecamatan Sipoholon Kabupaten Tapanuli Utara - SINAGA, DIANA RUMONDANG; ANTARA, MADE; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Analysis Added Value and BEP of Sihobuk Nuts in Silangkitang village, Sipoholon District of North Tapanuli Regency) Silangkitang village , Sipoholon district is one area in North Tapanuli potential in the development of home industry Sihobuk Nuts . This research aims to determine the processing of peanuts into Sihobuk Nuts ; the second to determine the added value obtained from processing peanuts into Sihobuk Nuts ; and third to know the constraints faced by entrepreneurs Sihobuk Nuts . Determination of ten home industry Sihobuk Nuts in Silangkitang village as an area of research census method , which means the entire population sampled , and all samples used as research respondents . The results showed that : (1) the processing peanuts into Sihobuk Nuts through the booking process raw materials, manufacture or processing, sorting nuts, product packaging and distribution products (2) the added value obtained from processing peanuts into Sihobuk Nuts is Rp 6353,94 (3) constraints faced by entrepreneurs is the difficulty of obtaining Sihobuk Nuts firewood and sorting and packing peanuts that mesih done manually. It is recommended that home industry Sihobuk Nuts maintaining the quality of the products because through the calculation of R / C Ratio is done to obtain greater value than one that is equal to 1.70, which means the business profitable. Keywords : processing, added value, constraints